丹戎布拉大学师范教育学院汉语专业 2017 届学生对汉语近义形容词的掌握情况 分析 - Sherly Wardhani; Lily Thamrin; Bun Yan Khiong (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractIn the learning process, because there are subtle differences between synonyms, students are likely to make mistakes in the collocation of similar adjectives in sentences, so I urged the author to investigate the students’ mastery of similar forms.Duo to the diverse classification of Chinese synonyms, so I research scope is limited to synonymous adjective. The function and meaning of adjectives is to distinguish the difference between things. If scholars can distinguish the subtle differences between synonyms, there will be no lack of meaning. This thesis obtains information by testing survey methods. Based on the result of the test analysis it can be concluded that students of the 2017 FKIP UNTAN Chinese language education study program have good mastery of mandarin adjective synonyms. The average correct rate of test questions is 60.47%.Keywords: Synonyms, Adjectives, Mastery